Efektivitas komunikasi jarak-jauh dalam melanjutkan pendampingan masyarakat: Pengalaman revegetasi gambut di tiga Kabupaten di Provinsi Riau - Ahmad Muhammad; Nurul Qomar; Radith Mahatma; Sigit Sutikno; Zuli Laili Isnaini; Muhammad Yusa (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Community engagement is often abruptly terminated as a project has to be officially ended following the termination of the fiscal year, which often leads to direct contact break off between project executors and their local counterparts. Consequently, a project initiated in the previous year may not persist in the following years. One strategy to cope with this problem is to use long-distance communication via handphone (HP) to continue the engagement of local counterparts. Our paper shares our experience as counterpart of Badan Restorasi Gambut (BRG) in engaging local communities carrying out peatland revegation in Bengkalis, Siak, and Kepulauan Meranti Regency of Riau. Revegetation was implemented as production and planting of natural forest tree seedlings. This paper evaluates the effectiveness of using long-distance communication for continuing our engagement in peatland revegetation. In our communications, technical and non-technical constraints of revegetation as well as the perceptions and expectations of our counterparts were discussed. We concluded, long-distance communication helps maintain “bonding” between project executors and their local counterparts, so that they do not feel left alone after a project has been formally terminated. Nevertheless, long-distance communication that is not accompanied with a real financial support to cover costs, eventually will not be sufficient.